THE INFLUENCE OF FEMALE DIRECTOR ON THE PROBABILITY OF COMPANIES EXPERIENCING FINANCIAL DISTRESS - Stephanie Angelina Koerniawan; Mariana Ing Malelak (Finance and Investment Program, School of Business and Management - Petra Christian University, 2020)
This study aims to determine the effect of Female Director on the Probability of a Company Experiencing Financial Distress. Springate model is used to predict the probability of a company experiencing financial distress. This study compares the effect of female director on the probability of a company experiencing financial distress without control variables and using control variables. The control variables in this study are board size, firm size and leverage. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2018. The samples in this study were 27 companies. The results of this study indicate that female directors have no significant effect on the probability of a company experiencing financial distress. By using control variables, it is shown that female directors do not significantly influence the probability of a company experiencing financial distress with the control variables such as board size, firm size, and leverage.